An Empirical Investigation Of Cold Email Marketing In The B2B Image Editing Industry: Insights From Dropicts - Rani, Fhadil Afdhani (Journal of Business, Management, and Social Studies, 2021)
Objective – This study aims to assess the effectiveness of the “collect and blast” cold email marketing method for a B2B company, specifically Dropicts, Pte. Ltd. Methodology – The primary data collection method was through a cold email campaign conducted over a four-month period. Quantitative analysis was performed on the collected data to assess the effectiveness of the cold email campaign. The study was limited to a single company and a specific time period, which may limit the generalizability of the findings. Findings – Despite sending a significant number of cold emails, the company achieved a very low conversion rate, with only two customers acquired after four months of intensive campaigning. This suggests that this particular marketing strategy is not an optimal approach for generating leads and acquiring new clients in the B2B image editing service industry. Novelty – The use of cold marketing as a business-to-business (B2B) strategy is a well-established practice. While the specific case study of Dropicts provides data on the performance of this method for an image editing service, the overall findings about the effectiveness of cold emailing align with general industry knowledge.